Learning Orientation as an Antecedent Towards Strategic Human Capital - Lee Jia Lin, Jocelyne; Hasliza, Halim; Ramayah, T. (2018)
Organisations need to deploy its resources to achieve sustainable competitive advantage. Strategic human capital is a resource that allows an organization to attain sustained competitive advantage. Creating strategic human capital however, is not easily done. There are elements that can be utilized to create a resource that helps the organization be distinguished from its competitors and this paper aims at examining the influence of learning orientation on strategic human capital among manufacturing organisations in Northern region of Malaysia. Learning has often been regarded as a source for sustainable advantage and is proposed to have a positive influence towards strategic human capital. This study adds to the present literature by explaining conceptually the linkages between learning orientation and strategic human capital. It also contributes to the literature by presenting the preliminary results of the study. The interview results will offer an introductory insight on the relationship between learning orientation and strategic human capital.